Table of contents, editorial board, and other front matter - Jim Shaner; Don Esslinger (Journal of Applied Communications, 1980)
Editorial front matter and table of contents for vol.63, no.3, July-Sept. (1980) of The ACE Quarterly, Official Journal of the Agricultural Communicators in Education